Kelayakan Finansial Usahatani Buah Naga Di Daerah Perkotaan Sebagai Alternatif Tambahan Pendapatan Petani - DEWI, IDA AYU LISTIA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018, 2018)
Financial Feasibility Of Dragon Fruits Farming In Urban Area As Additional Alternatives Of Farmer’s Revenues This study aims to analyze the financial feasibility of Dragon Fruit Farming in urban areas. Analyze the sensitivity of Dragon Fruit farming on the changes of production quantity, product selling price, and production cost. The pilot unit of Dragon Fruit Farming in urban area is in Experiment Garden of Faculty of Agriculture Udayana University. Key informants of this research are garden managers, field officers, field workers in Experimental Garden of Faculty of Agriculture Udayana University. The data used are Bank Rakyat Indonesia's interest rate, investment cost (seedling cuttings, climbers, used tires, rope, and equipment), operational cost (fertilizer and labor), production quantity, and product selling price. Data analysis used analysis of investment criteria and business sensitivity analysis. The results showed that the Dragon Fruit Farming in Experimental Garden of Faculty of Agriculture Udayana University was profitable so it was feasible to run. The value of farm income is Rp 231,453,087, Net B / C value is 4.03. IRR> I is 49.63%> 18%, the rate of payback for five years is eight months. This effort is very sensitive to the 50% decline in the selling price.